(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
A numerical investigation has been implemented to elucidate the effect of vertical and horizontal vibration at normal gravity on natural convection in a square enclosure filled with air at Rayleigh number 7×107 and 4× 108. The enclosure was comprised of two vertical and opposed surfaces (the right hot and the left cold) while the two other surfaces are adiabatic. The two-dimensional, low-Reynolds number k ? ???? turbulence model is applied to enable it to cope with low Reynolds number flows. By transforming the equation of (continuity, Navier-Stokes and energy) using finite volume method from differential forms to algebraic forms using SIMPLE algorithm with hybrid scheme dealing with the time term are adopted to solve the governing equations. A computer program in Fortran 90 was built to carry on the numerical solution. Three cases were studied in this work, case I(reaches to steady state and then begins the effect of vibration at each frequency), caseII and caseIII(begin the effect of vibration from the transient at ascending and descending frequencies respectively).After the validity of the present code by comparing results with these of previous study for similar conditions, solutions have been obtained for Prandtle number of 0.7, aspect ratio (A=1). In the high Rayleih number case (Ra=4×108), the gravitional thermal convection dominates, and the vibration motion does not enhances the heat transfer remarkably. In contrast, in low Rayleigh (Ra=7×107), the vibration thermal convection is dominant, and the vibration enhaces the heat transfer rate significantly. The effect of vertical directional vibration is more powerful in caseII(ascending frequency), when the horizontal directional vibration more effective in case III(descending frequency).